A Needs Analysis for Developing an AI-Supported EAP Learning Website in a Non-English Language Program - Binti Aisiah Daning Sumari (Universitas Islam Negeri Palopo, 2026)
English for Academic Purposes (EAP) is essential in higher education because it helps students understand academic texts and communicate effectively in academic contexts. However, students in non-English programs often struggle with academic reading and writing, and traditional lecture-based teaching provides limited support. Despite the growing use of educational technology, few studies have examined students’ academic English needs and their readiness to use AI-based learning tools in EAP. This study employed a descriptive exploratory mixed-methods design involving 48 undergraduate students from the Faculty of Language and Arts at the State University of Medan. Quantitative data were collected through a Likert-scale questionnaire with very high reliability (Cronbach’s alpha = 0.991), and qualitative data were gathered through semi-structured interviews. The results show a high level of perceived need (M = 4.07; 81.4%). Students reported strong needs related to academic literacy development, professional communication skills, structured learning support, and digital learning readiness. They also expressed positive attitudes toward AI features such as adaptive learning and personalized feedback. These findings support the development of a context-sensitive web-based EAP platform integrating adaptive AI features for academic language learning.